Developing a new breed of leaders - Drake, Jacquie; Turnbull James, Kim (Cranfield University School of Management, 2013)
What do Mark Carney, Ruby McGregor- Smith and Dr Andy Wood have in common? They are all exemplars of the new breed of leaders that we need for 21st century organisations.